Immigrants and Workplace Training: Evidence from Canadian Linked Employer Employee Data - Benoît Dostie; Mohsen Javdani (Institute of Labor Economics (IZA), 2019)
Job training is one of the most important aspects of skill formation and human capital accumulation. In this study we use longitudinal Canadian linked employer-employee data to examine whether white/visible minority immigrants and Canadian-borns experience different opportunities in two well-defined measures of firm-sponsored training: on-the-job training and classroom training. While we find no differences in on-the-job training between different groups, our results suggest that visible minority immigrants are significantly less likely to receive classroom training, and receive fewer and shorter classroom training courses, an experience that is not shared by white immigrants. For male visible minority immigrants, these gaps are entirely driven by their differential sorting into workplaces with less training opportunities. For their female counterparts however, they are mainly driven by differences that emerge within workplaces. We find no evidence that years spent in Canada or education level can appreciably reduce these gaps. Accounting for potential differences in career paths and hierarchical level also fails to explain these differences. We find however that these gaps are only experienced by visible minority immigrants who work in the for-profit sector, with those in the non-profit sector experiencing positive or no gaps in training. Finally, we show that other poor labor market outcomes of visible minority immigrants, including their wages and promotion opportunities, stem in part from these training gaps.
Keywords: J24; L22; M53; 330; immigrants; wages; firm-sponsored training; linked employer-employee data